Numerical study of comparing skirt sandpile with deep cement pile to improve load‒settlement response of circular footing in layered soils: Centric and eccentric effects - Hussein Ahmad (Heliyon)
This study investigates the performance of a skirt sand pile (SSP) system beneath a circular shallow footing using three-dimensional finite element analysis calibrated against a large-scale experimental setup. The SSP, measuring 8.00 m in length and 1.00 m in diameter, was analyzed in a soft clay-sandy soil environment. The Mohr–Coulomb, hardening soil, and linear elastic models were employed to simulate the soil and structural elements. The innovative aspect of this study lies in the comprehensive evaluation of the SSP system's load-bearing capacity and settlement behavior, revealing its superior performance compared to deep cement pile (DCP). Numerical results demonstrated LBR improvements of 1.7 and 1.4 at settlement ratios (s/B%) of 10 % and 15 %, respectively, for the SSP, compared to LBRs of 1.3 and 1.1 for DCM. Additionally, the study explores the significant Influence of increasing SSP length (by 180 %), which resulted in a much greater increase in load-bearing capacity compared to similar changes in DCM. Another key innovation is the analysis of soil cohesion and friction angle effects, where increasing these parameters resulted in a reduction in settlement ratios from 36 % to 12 %, with the load-bearing capacity improving from 2 to 3.7. A significant and innovative aspect of this study is the soil-skirt sandpile interaction, which was found to have a much greater effect on the load-bearing capacity and settlement behavior than the traditional soil-deep cement pile interaction. This study provides critical insights into the efficacy of SSP systems in enhancing foundation performance, offering a cost-effective, efficient alternative to traditional deep cement pile, especially in layered clay-sand soil environments. The findings provide practical guidance for optimizing foundation design and improving the sustainability of geotechnical engineering solutions.